Reliability, Validity, and Performance Characteristics of Elite Adolescent Athletes at Different Stages of Maturity in the 10 to 5 Repeated Jump Test - Baker, J.; Shillabeer, B.; Brandner, C.; Graham-Smith, P.; Mills, P.; Read, P. (Pediatric Exercise Science, 2022)
Reactive strength has been defined as an athlete`s capacity to bear a stretch load and change movement from a rapid eccentric to rapid concentric contraction (36) and provides an indication of fast stretch-shortening cycle (SSC) function (43). SSC actions produce more powerful contractions than concentric alone due to the storage and release of elastic energy and can be classified as either slow (over 250 ms) or fast (under 250 ms) depending on the duration of the ground contact time (GCT) (21,43). The fast SSC is utilized in many sporting movements such as running, sprinting, jumping, and hopping and can be quantified using the reactive strength index (RSI) (8). Practitioners can use this metric to monitor the effectiveness of training interventions and to determine neuromuscular readiness to perform (9). For example, RSI calculated from a drop jump was found to be more sensitive to training-induced fatigue than other commonly used tests, such as the countermovement jump (CMJ) and squat jump (7).